SCARB1 Gene Polymorphisms and HDL Subfractions in Coronary Artery Disease - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2018)
Background/Aim: Cardiovascular diseases are a leading cause of mortality and morbidity worldwide. Polymorphisms in the SCARB1 gene are known to be related to plasma lipids. Patients and Methods: Real time-polymerase chain reaction (RT-PCR) was used for identification of SCARB1 polymorphisms and the Lipoprint Quantimetrix System was employed in identification of HDL subfractions. Results: According to allelic distribution, in both groups SCARB1 AA genotype led to a two-fold decrease in the risk of developing cardiovascular disease (p=0.04), while the GA genotype increased the risk two-fold (p=0.03). According to the HDL subfraction analysis results, the AA genotype had higher levels of big-sized HDL subfraction (p=0.02). Conclusion: The SCARB1AA genotype decreased cardiovascular risk and carrying GA genotype and G allele increased the risk of CAD. AA genotype carriers had higher levels of big-sized HDL subfraction.
Keywords: Coronary artery disease; HDL subfractions; SCARB1; polymorphism; DENSITY-LIPOPROTEIN SUBFRACTIONS; SCAVENGER RECEPTOR; SR-BI; IDENTIFICATION; CHOLESTEROL; SEVERITY; RISK